The petunia MADS box gene FBP11 determines ovule identity. - Colombo, L (1995)
In contrast to the wealth of information relating to genes regulating floral meristem and floral organ identity, only limited data are available concerning genes that are involved in determining and regulating the identity and development of an ovule. We have recently isolated the floral binding protein 11 (FBP11) MADS box gene from petunia and found that it is expressed exclusively in ovule primordia and subsequently in the ovules, suggesting a role for this gene in ovule formation. To test this hypothesis, we constructed a recombinant gene in which the full-size FBP11 cDNA was placed under the control of a strong cauliflower mosaic virus 35S promoter. Transgenic petunia plants expressing this chimeric gene have ovulelike structures on the adaxial side of the sepals and the abaxial side of the petals. Detailed morphological studies showed that these ovulelike structures are true ovules. RNA gel blot analysis was performed to investigate ectopic FBP11 expression in relation to the expression of the closely related FBP7 gene and the putative petunia class C-type homeotic genes FBP6 and pMADS3. Our results indicate that FBP11 represents an ovule identity gene. A new model describing the mode of action of FBP11 as an additional class D MADS box gene is presented.